Geographical Analysis, Building Regulations in Indonesia, PP No: 16 of 2021 - Ch. Koesmartadi; B. Resti Nurhayati; M. Kusyanto (Architectural Research Journal, 2023)
Currently, Indonesia in regulating buildings refers to PP No: 16 of 2021, this regulation was made by the government. This regulation contains all the regulations regarding the layout of architectural forms, including the area limits relating to the area of the site and the allowable height limits. It is suspected that the concept of this regulation adopted from a European country so that its application often encounters problems, because the concept that is suspected of adopting one of the European countries has not been adapted to the geographical conditions of Indonesia. The regulation regulates the floor area which is calculated as the edge of the building with the percentage of the site area, even though for Indonesia's geographical conditions, shade is needed which takes up an additional area beyond the floor area. The rule regarding the height of the building is measured by the height of the top floor, even though according to Indonesia's geographical characteristics, where the sun passes through, it requires a roof that can reduce the heat and accelerate the drainage of rainwater. In Indonesia, which is known for its many varieties of architecture that follow local characteristics, it gets less attention. As a result, several traditional house architectural characters disappeared, which were quite numerous and varied. In this discussion, we look for formulas for building regulations that take into account geographical conditions and architectural variations